Rapid component of oxygen uptake kinetics is associated to rowing performance in competitive young rowers - Henriquez Olguin, C. F.; Tuesta Roa, M.; Morales Broerse, D.; Zepeda, Ruiz, H.; Báez San Martin, E. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Rowing performance is strongly influenced by rapid response to a step transition from rest to constant high intensity exercise. It has been suggested that the time constant of oxygen uptake (VO2) increase is closely reflected by the time constant for O2 utilization in the exercising muscles (1), suggesting that it could be related with performance (2). The aim of this work was to study the VO2 kinetics with non-linear analysis and its relation with rowing performance. Eleven elite young male rowers (16.1 ± 1.4 years) were included in the present study. First, VO2max and maximal aerobic power was determined by gas analysis (MetaLyzer 3-B, Cortex Leipzig, Germany) in an incremental test on rowing ergometer (Concept II- model C, Nottingham, UK) and, then, the VO2 kinetics was registered during a constant test at maximal aerobic power intensity (MAP). A mathematical model of VO2 max kinetics was processed in MATLAB software v7.12 (Natick, MA, USA), utilizing wavelet toolbox and optimization. The physiological signals were filtered through a De-noise of wavelet (daubechies 6) applied in first order. A triple exponential model of VO2 kinetic was calculated by equation proposed in previous studies (3) and adjusted through least-squared method. The time constant of II component (ôON) stands for the time constant of the fast component the time to reach 63% of the plateau of this phase during which physiological adaptations adjust to meet the increased metabolic demand. The rowing performance was determined in water conditions, during a 2000m test. The results were expressed as mean± standard deviation (SD)and pearson correlation was applied. The cardio-dynamic phase was not analyzed and slow component was not found in the VO2 signals. The ôON values observed were 24.09± 11.2 with amplitude of 53.1± 6.7 mL/kg/min during a limit time test at PAM. We found a significant correlation between velocity during a 2000m race and ôon of II component (r=0.9155 p <0.0001). Moreover, we observed the negative correlation between ôON with VO2 max (r= -0.8165 p <0.005). Our finding suggests, for first time, that ôON of rapid component of VO2 kinetics can be related with the aerobic capacity and performance of young rowers. This index may be useful for talent identification and training control.